ESL pre-service teachers’ evaluation of ESL web resources - Noraini Said (Human Resource Management Academic Research Society (HRMARS), 2021)
There is an amazing proliferation of ESL online materials ready to be utilized by learners and instructors. Sadly, users are commonly overwhelmed by the immense volume and therefore must critically evaluate the ones which are useful for them. This study reports on ESL preservice teachers’ evaluation of various ESL web-based resources for language learning and teaching in a Computer-Assisted Language Learning (CALL) course. 39 subjects participated in this study. Quantitative data was obtained from Son (2005) Language Learning Website Review Form which students completed, while video reviews and feedback forms produced by the students yielded qualitative data. 18 ESL resources were evaluated based on 15 evaluation criteria. Findings show that in overall, most ESL resources were deemed useful for language teaching and learning. However, four evaluation criteria were frequently cited with low rating such as authority, feedback, multimedia and communication. 17 from 18 ESL resources received high rating from the students. Video reviews validated data from students’ evaluation forms. Findings further reinforce the need for teachers and students to critically evaluate resources for their language learning and teaching.